The evaluation and validation of cell-mediated immunological responses for the improved detection of Mycobacterium bovis infection in African buffaloes (Syncerus caffer) - Smith, Katrin (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2021.